Authorities of The Governor of Bengkulu in Revorcing Mayor Regulation No. 43 of 2019 Concerning Classification of Basic Values of Land and Buildings as The Basis for Imposting Land and Building Rights Acquisition Fees - Pareke, JT Pareke; Fikri, Muhammad Darul; Putra, David Aprizon (NEGREI: Academic Journal of Law and Governance, 2024)
Authority is the power of govermment agencies and/or officials or others state administrators to act in the realm of public law. 1)what is the authority of the governor of bengkulu in revoking the mayor of bengkulu regulation no 43 of 2019 regarding the classification of the basic value of land and buildings as the imposition of a free for acquiring land and building rights. 2)The basic value of land and buildings as the basis for the imposition of fees for acquisition of land and building rughts. This type of research using a qualitative approach method. Data collection was carried out by means of interviews and documents from the regional govermment of bengkulu province. The results of the research are 1) the authority to repeal the mayor’s regulated in law no 23 of 2014, government regulation number 33 of 2018 and technically is authority is regulated in minister of home affairs regulations no 120 of 2018. 2) The Decree of the Governor of Bengkulu Number T.516.B.2 of 2021 concerning the Cancellation of the Mayor of Bengkulu Regulation Number 43 of 2019 concerning the Classification of the Basic Value of Land and Buildings as the Imposition of Fees for the Acquisition of Land and Building Rights is valid or invalid as regulated in Article 52 of the Law Number 30 of 2014 concerning Government Administration As amended by Law Number 11 of 2020 concerning Job Creation. Which in the law regulates the legal requirements of a decision which states the legal requirements for a decision are determined by an authorized official, made according to procedures, and the substance is in accordance with the object of the decision.